Purification and Characterization of Two Epoxide Hydrolases from Corynebacterium sp. Strain N-1074 - Nakamura, Tetsuji (1994)
Enzymes II(a) and II(b), which catalyze the conversion of epichlorohydrin (ECH) to 3-chloro-1,2-propanediol (MCP), were purified from Corynebacterium sp. strain N-1074, which catalyzes the formation of (R)-MCP from prochiral 1,3-dichloro-2-propanol via ECH. The specific activity of enzyme II(a) for the formation of MCP from ECH was about 6.4-fold higher than that of enzyme II(b). Both enzymes catalyzed the conversion of 1,2-epoxides to the corresponding diol, although they differed in several enzymatic properties.